Cascaded slice to volume registration for moving fetal FMRI - Seshamani, S.; Fogtmann, M.; Cheng, X.; Thomason, M.; Gatenby, C.; Studholme, C. (2013 IEEE 10th International Symposium on Biomedical Imaging, 2013)
Motion correction of MRI sequences is a very active area of research. Several postprocessing techniques for volume correction and more recently slice correction have been proposed. Slice motion correction of fMRI data typically involves iterative registration of slices to a target volume. The target volume is usually reconstructed at each iteration using current slice motion estimates, with all possible views of the subject. However, in the presence of large movements, the quality of the reconstruction can be greatly degraded without a good initialization, and this can in turn greatly affect the accuracy and precision of the slice registration. This paper introduces a cascaded motion correction pipeline that uses subsets of data to generate coherent volumes for initial target volume based slice registration in fMRI. The pipeline incorporates distortion correction, frame motion estimation and two levels of slice to volume registration. The proposed method has been tested on moving adult and fetal fMRI data.